Cytotoxin- and Chemotaxis-Genes Cooperate to Promote Adhesion of Photobacterium damselae subsp. damselae - von Hoven, Gisela; Neukirch, Claudia; Meyenburg, Martina; Schmidt, Sabine; Vences, Ana; Osorio, Carlos R.; Husmann, Matthias; Rivas, Amable J. (Frontiers in Microbiology, 2018)
Photobacterium damselae subsp. damselae (Pdd) is an emerging pathogen of marine animals that sometimes causes serious infections in humans. Two related pore forming toxins, phobalysins P and C, and damselysin, a phospholipase D, confer strong virulence of Pdd in mice. Because infections by Pdd are typically caused following exposure of wounds to sea water we investigated how salinity impacts toxin activity, swimming, and association of Pdd with epithelial cells. These activities were low when bacteria were pre-cultured in media with 3.5% NaCl, the global average salinity of sea water. In contrast, lower salinity increased swimming of wild type Pdd peaking at 2% NaCl, hemolysis, and association with epithelial cells peaking at 1–1.5%. Previously, we have found that hemolysin genes enhance the association of Pdd with epithelial cells, but the underlying mechanisms have remained ill-defined. We here searched for potential links between hemolysin-production, chemotaxis and association of Pdd with target cells at varying salt concentrations. Unexpectedly, disruption of chemotaxis regulator cheA not only affected bacterial swimming and association with epithelial cells at intermediate to low salinity, but also reduced the production of plasmid-encoded phobalysin (PhlyP). The results thus reveal unforeseen links between chemotaxis regulators, a pore forming toxin and the association of a marine bacterium with target cells.